Do shared semantic features facilitate Lexical-semantic processing in early course psychosis? - Sekulić Sović, Martina; Erdeljac, Vlasta; Kužina, Iva (Clinical linguistics & phonetics, 2020)
The lexical-semantic relatedness effect supposes different activation in the semantic memory of related versus unrelated word-pairs. Semantically related pairs are considered to result in a larger spread of activation as the activation of concept nodes is dependent on shared lexical-semantic features of concepts. The increased activation of concepts in the semantic memory in individuals with schizophrenia is found to be, faster spreading and lacking in inhibition in relation to healthy control subjects. The aim of this study was to examine whether the lexical-semantic relatedness effect influences processing in individuals with early course psychosis by utilizing an explicit semantic matching task with 0ms SOA (Stimulus Onset Asynchrony) to analyse the strategy-free automatic spreading activation process. Overall, the patient group had lower accuracy and longer reaction times compared with healthy subjects, as well as better accuracy for related word-pairs and longer reaction times are for unrelated word-pairs. In clinical practice, the determination of language classifiers for early course psychosis could potentially enable the creation of reliable diagnostic markers and instruments for identifying the population with an elevated risk ofdeveloping disorders within a spectrum of schizophrenia, and predicting the course of the disorder.